Intralesional measles, mumps, and rubella vaccine versus cryotherapy in treatment of warts: A prospective study - Harish M Rajegowda; Deepadarshan Kalegowda; Shashi K B. Madegowda; Jayashree K Palanayak (Wolters Kluwer Medknow Publications, 2020)
Background: Warts are benign tumors caused by infection of keratinocytes with human papillomavirus. Various modalities are available for the treatment of cutaneous warts such as destructive procedures, surgical methods, and immunotherapy. Recently, immunotherapy with intralesional antigens/vaccines is emerging as a novel method with encouraging results. Purpose: The study aimed to compare the efficacy of intralesional mumps, measles, and rubella (MMR) vaccine versus cryotherapy in the treatment of cutaneous warts. Methods: In this prospective study, 60 clinically diagnosed cases of cutaneous warts were enrolled and randomly divided into two groups of 30 each. Patients of Group A received 0.5 ml of reconstituted MMR vaccine, which was injected into the largest wart. The dose was repeated at 3-week intervals until complete clearance or for a maximum of 3 doses. In Group B, patients received cryotherapy with liquid nitrogen at weekly intervals for a maximum of 9 sessions. Patients of both the groups were followed up at the 3rd, 6th, and 9th weeks to evaluate clinical outcome on the Visual Analog Scale. Statistical analysis was done by the Chi-square test using SPSS software. Results: Out of 30 patients, 63.3% (19) of the patients of Group A showed complete clearance of warts compared with 33.3% (10) of the patients of Group B at the end of 9 weeks. Adverse effects were more with cryotherapy including pain, blistering, and depigmentation, whereas immunotherapy was well-tolerated except for the pain during injection. Conclusion: Intralesional MMR vaccine immunotherapy was more effective, with an added advantage of regression of distant warts, fewer sessions, and no serious side effects.